2021
DOI: 10.1002/cssc.202101175
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Driven Waste‐To‐Value Upcycling: Bio‐Based Polyols and Polyurethanes from the Photo‐Oxygenation of Cardanols

Abstract: The upcycling of waste biomass into valuable materials by resource‐efficient chemical transformations is a prime objective for sustainable chemistry. This approach is demonstrated in a straightforward light‐driven synthesis of polyols and polyurethane foams from the multi‐ton waste products of cashew nut processing. The photo‐oxygenation of cardanol from nutshell oil results in the formation of synthetically versatile hydroperoxides. The choice of the workup method (i. e., reduction, hydrogenation, epoxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…3-Ethyl-2-pentene was converted to a mixture of products (entry 6). Although a 2% yield was obtained in the batch system after 10 h, yields of 30.9% (9) and 23.1% (10) were obtained in the continuous-flow system.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…3-Ethyl-2-pentene was converted to a mixture of products (entry 6). Although a 2% yield was obtained in the batch system after 10 h, yields of 30.9% (9) and 23.1% (10) were obtained in the continuous-flow system.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Epoxy alcohols are valuable building blocks for organic synthesis. For instance, their semipinacol rearrangements are useful alternatives to aldol and related reactions for synthesizing β-hydroxycarbonyl compounds. To date, considerable effort has been directed toward improving the synthetic routes to epoxy alcohols, as exemplified by the eco-friendly method reported by Adam and Nestler. According to this method, the hydroperoxides, generated via the photooxygenation of alkenes using green, nontoxic, and inexpensive O 2 gas, are converted to epoxy alcohols through secondary epoxidation in the absence of additional oxidants. However, further research on the combination of the first (photooxygenation) and second (epoxidation) steps is required to reduce the reaction time and improve product yields.…”
Section: Introductionmentioning
confidence: 99%
“…A future of using edible oils as a major alternative to petrochemical polyol may pose a critical issue of competition with food supplies. It is also possible to use non-edible vegetable oils such as Karanja oil [ 13 ], tung oil [ 17 , 18 ], tall oil [ 19 , 20 , 21 , 22 , 23 ] and cardanol [ 24 , 25 ]. Luo et al reported the feasibility of using crude glycerol in biopolyol synthesis and the production of PUR foams with apparent density of 43 kg/m 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this system, Li et al 24 added natural thylakoid membranes (TMs) and polyphosphate:AMP phosphotransferase for the simultaneous light-driven regeneration of NADPH and ATP. However, this ivSEB might suffer from substrate inhibition 24 , tedious preparation and instability of TMs, and reduced light penetration efficiency during scale-up 25 . Zhang et al designed a chemical-biological hybrid pathway to produce PHB from carbon dioxide (CO 2 ), in which an ivSEB was used to convert the CO 2 -derived methanol to PHB 26 .…”
Section: Introductionmentioning
confidence: 99%